1994
DOI: 10.1093/oxfordjournals.annonc.a058725
|View full text |Cite
|
Sign up to set email alerts
|

Antibody directed enzyme prodrug therapy (ADEPT)

Abstract: The concept of generating cytotoxic agents from non-toxic prodrugs at tumour sites by antibody vectored enzyme introduces a wide range of opportunities. Various prodrug-enzyme combinations have been described and encouraging results reported in xenograft models. Whilst the mouse model is a valuable tool in this approach translation to the human patient may expose more complex issues. The objective of restricting drug action to tumour sites and thus allowing greatly increased cytotoxic action requires more prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 66 publications
0
28
0
2
Order By: Relevance
“…A partir de então, a mostarda (17) vem sendo estudada utilizando-se o sistema ADEPT (AntibodyDirected Enzyme Prodrug Therapy) 89 . Esta terapia fundamenta-se na ativação enzimática de um pró-fármaco usando um conjugado anticorpo-enzima (AEC) específico para antígenos presentes na membrana das células tumorais 90,91 . Neste caso, a enzima utilizada é a nitrorredutase de E. coli.…”
Section: Outras Classes De Agentes Biorredutíveisunclassified
See 1 more Smart Citation
“…A partir de então, a mostarda (17) vem sendo estudada utilizando-se o sistema ADEPT (AntibodyDirected Enzyme Prodrug Therapy) 89 . Esta terapia fundamenta-se na ativação enzimática de um pró-fármaco usando um conjugado anticorpo-enzima (AEC) específico para antígenos presentes na membrana das células tumorais 90,91 . Neste caso, a enzima utilizada é a nitrorredutase de E. coli.…”
Section: Outras Classes De Agentes Biorredutíveisunclassified
“…Neste caso, a enzima utilizada é a nitrorredutase de E. coli. Em linhas gerais, após administração e distribuição pelo organismo, o AEC liga-se às células tumorais e, em seguida, administra-se a mostarda (17) (pró-fármaco) 90 . Esta é, então, reduzida pela nitrorredutase acoplada ao anticorpo, liberando a mostarda na sua forma ativa (Figura 15), na região do tumor 89 .…”
Section: Outras Classes De Agentes Biorredutíveisunclassified
“…The phenol mustard drug liberated from PGP andFTP by CPG2 is some 50-to 100-fold more potent than the benzoic acid mustard drug liberated from the CMDA prodrug (Springer et al, 1991b;Blakey et al, 1993) which is currently in chnical trials combination with the F(ab%A5B7-CPG2 conjugate (Bagshawe et al, , 1995Bagshawe, 1993 (Springer et al, 1991b Previously, Wallace and Senter (1991) reported an ADEPT system which incorporated a different prodrug of the phenol mustard drug used in these studies. The prodrug wasp[NVNBis(2chothyl)aminonyl phosphate (POMP) and the enzyme used to cleave the phosphate residue to release the drug was alkaline phosphatase.…”
Section: E;nzyme Kineticsmentioning
confidence: 99%
“…The activity of this system was probablylimited by endogenous alkaline phosphatase causing conversion of prodrug to drug and so enhancing toxicity. Since CPG2 is a bacterial enzyme and no active drug has been detected following the administration of the CMDA prodrug to patients in the absence of conjugate (Bagshawe, 1993;Bagshawe et al, 1995 …”
Section: E;nzyme Kineticsmentioning
confidence: 99%
“…Antibody directed enzyme prodrug therapy (ADEPT) is a targeted therapeutic method based on antibody-enzyme conjugates and prodrugs [1,2], which is a promising approach for targeting treatment of cancer. It is designed to restrict the action of cytotoxic agents at the tumor sites.…”
Section: Introductionmentioning
confidence: 99%